Exchange coupling and coercivity enhancement in cuprate/manganite bilayers - Wu, Tom (2013)
We report on the magnetic properties of cuprate/manganite bilayers composed of antiferromagnetic (AFM) La2CuO4 and ferromagnetic La0.70Sr0.30MnO3. The temperature dependent magnetization data indicate an interfacial spin-glass state. Furthermore, the bilayer exhibits significant enhancement of coercivity compared to the La0.70Sr0.30MnO3 single layer and reaches 705 Oe at 5 K. The dependence of coercivity on the AFM layer thickness indicates that the enhancement cannot be explained by the interfacial charge diffusion. Our results suggest that the exchange coupling between Mn and Cu spins and the magnetic frustration at the La2CuO4/La0.70Sr0.30MnO3 interface must be considered to harness the properties of cuprate/manganite heterostructures.